What Common Agricultural Policy after Brexit? - Roederer-Rynning, Christilla (2019)
Suppose we were in 2028: what would the Common Agricultural Policy (CAP) look like then? Would it be significantly different from the policy we know today? How, and why? And to what extent would Brexit have catalyzed these changes? The CAP is one of the founding policies of the EU and a strategic lever to address critical 21st century challenges such as climate change and the rising demand for food at the global level. It also has an important role in Europe to address the growing urban-rural divide and its potentially destabilizing impact on European politics. In this article, we examine the impact of Brexit from a political-economic perspective emphasizing the multi-level context within which the CAP is embedded. As an EU member state, the UK found a way to partly accommodate the CAP to its needs even though this policy was a source of intense UK dissatisfaction with the EU. Post-Brexit, the budgetary and market implications of the UK’s departure may favour positions that support a return to a more traditional policy of farm income support. On the other hand, more radical farm policies in England and Wales could partly offset these effects by setting the agenda for continued CAP reform, if they are seen to be successful.